Growth and yield of tomato as affected by organic and inorganic fertilizers (Journal of the Bangladesh Agricultural University, 2019)
Unscrupulous use of synthetic fertilizers are not only increasing cost of tomato production but also decreasing tomato yield and quality, deteriorating soil health and environment. Organic manures can produce quality product as well as maintain soil health.  Considering this verity an experiment was carried out at the Dr. Purnendu Gain Field Laboratory of Agrotechnology Discipline, Khulna University, Khulna to evaluate the performance of tomato crop under application of different organic and inorganic fertilizers. The experiment was designed in RCBD using two varieties (BARI Tomato-14 and BARI Tomato-15) and eight treatments [i) 100% Recommended fertilizer dose (RFD) for N, P and K; ii) 100% cowdung (CD); iii) 100% poultry manure (PM); iv) 100% vermi-compost (VC); v) 100% Mustard oil cake (MOC); vi) 100% organic manures (25% of each of CD , PM , VC and MOC); vii) 80% organic manure (20% of each of CD, PM, VC and MOC) + 20% RFD; viii) 60% organic manure (15% of each of CD, PM, VC and MOC) + 40% RFD].The tallest plant (77.5 cm) with maximum fruit length (5.98 cm), maximum number of flower clusters plant-1 (16.24), number of flowers cluster-1 (13.07), number of fruit clusters plant-1 (8.20) and number of fruits cluster-1 (6.97) were observed from combined effect of 60% organic manures with 40% RFD in BARI Tomato-15. On the contrary, this treatment produced maximum fruit diameter (6.29cm), maximum weight of individual fruit (91.43g) and the highest yield (87.17 t/ha) in BARI tomato-14. From economic point of view, maximum net return (Tk. 841345) as well as benefit cost ratio (5.11) was also observed from 60% organic manure + 40% RFD. Thus, BARI tomato-14 with combination of organic manures (60%) and inorganic fertilizers (40%) provided better performance concerning growth, yield and economic aspects.J Bangladesh Agril Univ 17(4): 500–506, 2019